The personal and organizational factors who influence the creativity of the personnel - DANI , Safaâ; FARIDI , Mohamed (Revue Internationale du Chercheur, 2020)
The purpose of this article is to identify the personal and organizational factors that influence creativity of employees. On this research we defined three hypotheses and we aim to analyze the effect of this three factors: intrinsic motivation, encouragement of management and autonomy at work on creativity. We opted for a quantitative survey, our target is 131 employees, interviewed face-to-face in three railway stations: Brussels-South, Liège-Guillemins and Charleroi-South stations After analyzing the data, our three hypotheses were confirmed.